1974
DOI: 10.2307/3896504
|View full text |Cite
|
Sign up to set email alerts
|

Cover-Weight Relationships

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Individual lifeform annual productions were determined by multiplying average percentage cover values by lifeform (Payne 1974;Olson and Martin 1981) for each stand, treatment, sampling period, and year combination by the total understory vegetation annual production amount. See VanderSchaaf et al (2000) for a description of percentage cover methodology and results.…”
Section: Vegetation Measurementsmentioning
confidence: 99%
“…Individual lifeform annual productions were determined by multiplying average percentage cover values by lifeform (Payne 1974;Olson and Martin 1981) for each stand, treatment, sampling period, and year combination by the total understory vegetation annual production amount. See VanderSchaaf et al (2000) for a description of percentage cover methodology and results.…”
Section: Vegetation Measurementsmentioning
confidence: 99%
“…Relative percent species composition by weight used in the range condition analysis method favors plants that produce more biomass, while the Ecodata system emphasizes canopy cover. Payne (1974) found that the average correlation of cover and weight was 0.62 for all grass species and provided evidence that correlations between weight and cover could vary from R = 0.98 to R = 0.14 depending on the individual plant species. Therefore, differences between ecological status scores and range condition scores could be due to variable correlations between plant weight and canopy cover.…”
Section: Discussionmentioning
confidence: 78%
“…In mountain ranges of southwestern Montana, Payne (1974) found a significant correlation greater than 0.90 between canopy cover and herbage weight for 16 species. Only six species showed a significant correlation coefficient (r) less than 0.7.…”
Section: Covermentioning
confidence: 82%